Somali, Muslim, British: striving in securitized Britain - Liberatore, Giulia (Monographs on social anthropology, 2017)
"Somalis are one of the most chastised Muslim communities in Europe. Frequently depicted in the news as victims of female genital mutilation, perpetrators of gang violence, or as jihadi brides and radical Islamists, Somalis have long been seen as a problematic refugee community in Britain and beyond. Somali, Muslim, British shifts attention away from these public debates to provide a detailed ethnographic study of the lives of Somali Muslim women in the United Kingdom. Based on ethnographic research with 21 households in London, it explores the aspirations of Somali women and how these shift over the course of the life cycle and across generations. It argues that these women's aspirations are shaped by, but also unsettle, contemporary ideas of religion, culture and nationality. Giulia Liberatore demonstrates that the increasing dominance of Islamic piety in Europe cannot be explained solely through the lens of religion and migration. Instead, it needs to be understood as one among many different forms of striving - such as for modernity or financial security - that individuals pursue throughout their lives. Bringing new perspectives to debates about Islam, multiculturalism, integration, and national identity in Europe and beyond, this book makes an important contribution to the anthropology of religion, subjectivity, and gender"--